2020
DOI: 10.3389/fpsyg.2020.551131
|View full text |Cite
|
Sign up to set email alerts
|

(In)Sensitivity to Accuracy? Children’s and Adults’ Decisions About Who to Trust: The Teacher or the Internet

Abstract: Recent research has challenged the extended idea that when presented with conflicting information provided by different sources, children, as do adults, make epistemic judgments based on the past accuracy of each source. Instead, individuals may use relatively simple, but adaptive non-epistemic strategies. Here we examined how primary-school children ( N = 114) and undergraduate students ( N = 57) deal with conflicting information provided by two key sources of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(38 reference statements)
0
3
0
2
Order By: Relevance
“…The resulting synthesis is displayed in Table 1 . See Supplementary Table 1 (Barth et al ., 2014 ; Bascandziev & Harris, 2014, 2016 ; Baumann et al ., 2023 ; Bernard et al ., 2012 ; Bernard et al ., 2014 ; Bernard et al ., 2016 ; Bincoletto et al ., 2023 ; Birch et al ., 2008 ; Bo et al ., 2017 ; Boseovski & Thurman, 2014 ; Bridgers et al ., 2016 ; Brink & Wellman, 2020 ; Brosseau-Liard & Birch, 2010 , 2011 ; Brosseau-Liard et al ., 2015 ; Brosseau-Liard, et al ., 2018 ; Butler et al ., 2018 ; Campbell et al ., 2021 ; Castelain et al ., 2016 ; Chan & Tardif, 2013 ; Clegg et al ., 2019 ; Clément et al ., 2013 ; Corriveau et al ., 2009 ; Corriveau et al ., 2011 ; Corriveau et al ., 2013 ; Corriveau & Harris, 2009a , 2009b ; Corriveau & Kurkul, 2014 ; Danovitch & Alzahabi, 2013 ; Danovitch & Mills, 2014 ; Ding et al ., 2022 ; Doebel et al ., 2016 ; Durkin & Shafto, 2016 ; Echterhoff et al ., 2017 ; Einav, 2014 ; Einav et al ., 2020 ; Einav & Robinson, 2010 ; Elashi & Mills, 2014 ; Fedra & Schmidt, 2019 ; Fitneva & Dunfield, 2010 ; Frenken & Imhoff, 2022; Fusaro & Harris, 2008; Gierth & Bromme, 2020 ; Gilbert et al ., 1990 ; Gilbert et al ., 1993 ; Ghossainy et al ., 2021 ; Guerrero et al ., 2017 ; Guerrero et al ., 2019 ; Guerrero et al ., …”
Section: Resultsunclassified
See 1 more Smart Citation
“…The resulting synthesis is displayed in Table 1 . See Supplementary Table 1 (Barth et al ., 2014 ; Bascandziev & Harris, 2014, 2016 ; Baumann et al ., 2023 ; Bernard et al ., 2012 ; Bernard et al ., 2014 ; Bernard et al ., 2016 ; Bincoletto et al ., 2023 ; Birch et al ., 2008 ; Bo et al ., 2017 ; Boseovski & Thurman, 2014 ; Bridgers et al ., 2016 ; Brink & Wellman, 2020 ; Brosseau-Liard & Birch, 2010 , 2011 ; Brosseau-Liard et al ., 2015 ; Brosseau-Liard, et al ., 2018 ; Butler et al ., 2018 ; Campbell et al ., 2021 ; Castelain et al ., 2016 ; Chan & Tardif, 2013 ; Clegg et al ., 2019 ; Clément et al ., 2013 ; Corriveau et al ., 2009 ; Corriveau et al ., 2011 ; Corriveau et al ., 2013 ; Corriveau & Harris, 2009a , 2009b ; Corriveau & Kurkul, 2014 ; Danovitch & Alzahabi, 2013 ; Danovitch & Mills, 2014 ; Ding et al ., 2022 ; Doebel et al ., 2016 ; Durkin & Shafto, 2016 ; Echterhoff et al ., 2017 ; Einav, 2014 ; Einav et al ., 2020 ; Einav & Robinson, 2010 ; Elashi & Mills, 2014 ; Fedra & Schmidt, 2019 ; Fitneva & Dunfield, 2010 ; Frenken & Imhoff, 2022; Fusaro & Harris, 2008; Gierth & Bromme, 2020 ; Gilbert et al ., 1990 ; Gilbert et al ., 1993 ; Ghossainy et al ., 2021 ; Guerrero et al ., 2017 ; Guerrero et al ., 2019 ; Guerrero et al ., …”
Section: Resultsunclassified
“…A total of 9 studies reported similar results in non-clinical adults as those in studies of children’s selective trust. Adults were found to also selectively trust claims supported by good evidence and from sources who show confidence and a history of accuracy (Fitneva & Dunfield, 2010 ; Gierth & Bromme, 2020 ; Guerrero et al ., 2020 ; Pozzi & Mazzarella, 2023 ; Ronfard & Lane, 2019 ; Tenney et al ., 2011 ). Clément et al ( 2013 ) found in their experiments that adults, similarly to 3-year-olds, preferred to acquire new knowledge from an avatar displaying a happy face than from an avatar displaying an angry face.…”
Section: Resultsmentioning
confidence: 99%
“…Casi la mitad de ellos afirmó que podría identificar si la información es o no falsa con solo leer el contenido. Esta idea, que hemos incluido en la categoría denominada 'conocimiento previo', puede considerarse equivalente a 'aplicar el sentido común', criterio que muchos adultos empleamos para decidir si confiar o no en una pieza de información (e.g., Guerrero et al, 2020). Sin embargo, la diferencia con lo observado en adultos es el nivel de sofisticación de esta estrategia.…”
Section: Discussionunclassified
“…Almost half the participants claimed they could identify the false information just by reading the content. Tentatively, this idea, which we included in the category of ‘prior knowledge’, may be considered equivalent to ‘applying common sense’, a criterion used by many adults to decide whether to trust a piece of information or not (e.g., Guerrero et al, 2020). Indeed, children and adults differ greatly in the level of sophistication of this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one recent study has explored how providing inaccurate information affects children's trust in the internet and/or a teacher – informants belonging to different ontological categories. Guerrero et al (2020) found that after viewing an image of the Google homepage and a photo of their real science teacher, and then observing either the Google search engine or their teacher providing an inaccurate answer to a simple question, 7‐years‐olds showed no preference for a previously accurate/inaccurate teacher and the inaccurate/accurate internet when judging answers to subsequent questions but 10‐years‐olds, unexpectedly, were actually more willing to endorse the previously inaccurate source. However, in this study, the internet or teacher provided only one piece of incorrect information, and the teacher was represented by a photo of the children's own teacher.…”
Section: Introductionmentioning
confidence: 99%